Modelling of continuous L-malic acid production by porcine heart fumarase and fumarase in yeast cells - Vrsalović Presečki, Ana (Array, 2009)
Summary: Continuous production of L-malic acid will be presented in this paper. The fumarase isolated from porcine heart, fumarase in the permeabilized non-growing cells of baker’s yeast and Saccharomyces bayanus (UVAFERM BC) were used as biocatalysts. In the production of L-malic acid with fumarase isolated from porcine hearts, there was no enzyme deactivation for a period of two days. At the average residence time of 4 hours, the conversion of about 80 % was achieved. Inactivation of the enzyme was observed using permeabilized cells. This inactivation is described as a reversible process. Conversion of about 50 % was achieved with the remaining enzyme activity. A mathematical model that describes the production of L-malic acid, which contains the enzyme inactivation rate, was developed. Based on simulations, the used biocatalysts were compared. The results show that in the continuous production of L-malic acid, one milligram of purified enzyme corresponds to 68 g (wet weight) cells of Saccharomyces bayanus or 120 g (wet weight) cells of baker’s yeast